(untitled) (African Journal of Biomedical Research, 2020)
Routine check and optimal control of blood pressure have been recommended to reduce the high cardiovascular disease burden in the Southern Pacific. As demographic profile in the Pacific Island countries continues to transition, the burden of cardiovascular disease is importunately affecting more younger and high stress population. In collaboration with the Healthy Setting Initiative of the Ministry of health, we conducted a survey of blood pressure among market traders in Suva City Central and Nasouri markets of Fiji Islands. Following ethical approval and informed consent, we obtained socio-demographic data, and measured anthropometric indices and blood pressure of asymptomatic adult market traders of Suva City and Nasouri market using standard procedures. Participants comprised of 189 traders (52% females); with mean body mass index of 30kg/m2, weight of 82kg and waist circumference of 101cm. Overall, 152(80%) had sub-optimal blood pressure: elevated 23(12%), stage I: 70(37%), stage II: 57(30) and hypertensive crisis 2(1%). Of these, 30(20%) reported being compliant with medication, 62(41%) non-compliant and 60(39%) were previously unaware of their blood pressure status. Percent body fat (OR: 1.07; 95% CI: 1.02-1.13) and diastolic blood pressure (OR: 1.34; 95% CI: 1.21-1.48) were independently associated with hypertension. Burden of hypertension is high (80%) among study participants, with 39% of these being undiagnosed. There are issues with suboptimal blood pressure control and non-compliance with medication among study participants. There is need for health education, routine screening and sustainable intervention to reduce this burden among this population